Evaluation Of Ship Needs On The Galala – Namlea Route, Maluku Province - Santoso; Kodrat Alam; Nyayu Tiara Hairani (IWTJ : International Water Transport Journal, 2022)
Galala Ferry Port is a located in Galala Village, Sirimau District, Ambon City which serves the Galala - Namlea route. There are two Ro-Ro ships operating on this route with a total of seven trips per day. The distance for the Galala – Namlea traffic crossing is 85 miles. However, the operation of the ship on a fairly long route is not matched by the ideal number of trips so that there is a buildup of vehicles and service users who are not in the right place. The average time needed to sail is 8 hours. This study aims to determine the ship's load factor, to determine ship productivity, and to arrange ship schedules based on the number of ship trips. Then analyzed using several analytical methods to overcome these problems, including load factor analysis, analysis of population and vehicle growth predictions for the next 5 years using simple linear regression, ship frequency analysis, analysis of the need for the number of ships, and scheduling analysis. From this analysis, it can be concluded that the operating ship shows a load factor that exceeds the ideal capacity of the ship, which is 65% where there are conditions that are not proportional to the number of requests for service users and the frequency of existing ships. So it is necessary to add trips and the number of ships to suit the conditions in the field.